Effects of mutual grafting on the cadmium accumulation characteristics of two ecotypes of Solanum photeinocarpum. Issue 5 (16th April 2019) - Yao, Huan; Zhang, Fenqin; Qing, Mei; Chen, Maolin; Lu, Zicheng; Zhang, Qian; Lin, Lijin; Liao, Ming'an; Chen, Shengxiang; Huang, Zhi; Chen, Cheng; Ren, Wei
Abstract: The effects of mutual grafting on the cadmium (Cd) accumulation characteristics of two ecotypes (farmland and mining) of the potential Cd-hyperaccumulator Solanum photeinocarpum were studied through a pot experiment for one month. Four treatments were used in the experiment: ungrafted farmland ecotype (F-CK), ungrafted mining ecotype (M-CK), the farmland ecotype as the scion grafted onto rootstocks of the mining ecotype (F-Scion), and the mining ecotype as the scion grafted onto rootstocks of the farmland ecotype (M-Scion). Mutual grafting increased the rootstock biomass of both S. photeinocarpum ecotypes. However, mutual grafting decreased the scion biomass of F-Scion compared with F-CK and M-CK, and the scion biomass of M-Scion was higher than that of M-CK and lower than that of F-CK. The Cd content in the rootstock of M-Scion increased compared with F-CK, and the Cd content in the rootstock of F-Scion increased compared with M-CK, but mutual grafting decreased the Cd content in scions of both S. photeinocarpum ecotypes. Mutual grafting increased Cd extraction by rootstocks of both S. photeinocarpum ecotypes, but decreased extraction by scions. Therefore, mutual grafting can increase Cd accumulation in S. photeinocarpum rootstocks but not increase Cd accumulation in S. photeinocarpum scions in a short period.